Problematika Pengelolaan Baitul Mal Wat Tamwil (BMT) dan Implikasinya terhadap Perlindungan Nasabah - Ulum, Muh. Bachrul (Fakultas Syariah IAIN Purwokerto, 2007)
BMT as a micro finance institution faces some obstacles, not only internal but also external in condusive condition. Those obstacles are ranged in some institution aspects and they causes a variety of LKM , restricted law framing, lack of rules, lack of guidance and supervision, different status since this institution is not integrated yet to the formal finance institution, and there is not any ‘buffer’ or a guarantee of saving. Those show a weak protection for BMT customers.